Comparative and development public administration 2000: introduction to the symposium - Farazmand, Ali (1998)
The twin fields of comparative and development administration have been major components of public administration, both theoretically and practically. Their development as fields of study has proliferated since World War II, and reached a peak during the 1960s with the Comparative Administration Group (CAG). Despite major achievements, comparative and development administration experienced a major decline in the 1970s. However, a resurgence of interest in both subfields of public administration has emerged since the 1980s, and the number of scholarly works in these areas is impressively increasing. This trend will continue with significant contributions to the knowledge in the field by the year 2000. - Reproduced
Keywords: Public administration